RESISTANCE EVALUATION OF MODERN RICE VARIETIES TO BROWN PLANTHOPPER Nilaparvata lugens STÃ…L - Iswanto, Eko Hari; Munawar, Dede; Rahmini, Rahmini (Universitas Lampung, 2020)
Resistance evaluation of modern rice varieties to brown planthopper Nilaparvata lugens STÃ…L. The research was performedto understand the resistance of modern rice varieties to the field population of brown planthopper (BPH). The researchstudied BPH settling preference, numbers of laid eggs, and functional plant loss index (FPLI) of resistant and susceptible ricevarieties. The results showed BPH were less settle and laid fewer eggs on resistant varieties. BPH significantly settled longeron TN1 than other varieties after 24 hours. The numbers of eggs laid on rice resistant varieties (Inpari 13, Inpari 31, Inpari 33,RH, and PTB33) were fewer compared to TN1. FPLI value in TN1 was the highest among the tested rice varieties. Inpari 13 hadbetter resistance to BPH compared to Inpari 31 and Inpari 33. In managing BPH in endemic areas, we recommend Inpari 13,Inpari 31, and Inpari 33 to be planted in rotation.